Use of a dynamic method in calibration of dye-dilution curves during cardiac surgery. - Lin, Y T (1975)
A simplified dynamic method of calibration for dye-dilution curves is described. The method involves appropriate matching of the fluid volume in the mixing chamber, the blood withdrawal rate, and the calibration dose of dye. It was used to compare the observed versus calibrated pump output of a heart-lung machine with individual dye-dilution curves obtained from 15 patients during total cardiopulmonary bypass. The results indicate that the difference (range+14% to-8%) between the two is statistically insignificant. The method is rapid and relatively simple. It is particularly useful for cardiac output determination during unsteady clinical conditions because of the ability to calibrate dye curves at the time they are recorded.